Membangun Budaya Sadar Bencana melalui Komunikasi Mitigasi pada Masyarakat Desa Cijengkol, Subang, Jawa Barat - Imaddudin Imaddudin; Wa Ode Sitti Nurhaliza; Titis Nurwulan Suciati; Asrul Nur Iman; Aan Widodo; Syahrul Hidayanto; Fadli M. Athalarik (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Concern for disasters has become the consciousness of every individual, including the people of Cijengkol Village, Subang, West Java. Moreover, disasters can occur at any time and disrupt people's life patterns. This readiness continues to be communicated so that mitigation for all elements of society can be understood and implemented. Through the delivery of information and education in the form of counseling, it is hoped that it can build a culture of awareness of natural, non-natural and social disasters. This counseling method is carried out directly from the initial discussion of the problem to counseling and evaluation which is part of community service activities. As a result, the people of Cijengkol Village, Subang, West Java were cognitively able to understand disasters and their types and became a concern for joint anticipation. Meanwhile, effectively and conatively are not yet completely binding, elements of society should also act as saviors, not wanting to be saved as the main mindset. So that disaster awareness no longer belongs to stakeholders but to the general public who fully implement it.